Recent updates on correlates of vaccine-induced protection - Plotkin, Stanley A. (Frontiers in Immunology, 2023)
Correlates of protection are key for vaccine development against any pathogen. In this paper we summarize recent information about correlates for vaccines against dengue, Ebola, influenza, pneumococcal, respiratory syncytial virus, rotavirus, shigella, tuberculosis and Zika virus.